Survei Self Confidence Servis Bawah dalam Pembelajaran Bola Voli pada Siswa SMPN 2 Jayakerta - Dimas Ibnu; Nana Suryana Nasution; Febi Kurniawan (Universitas Singaperbangsa, 2021)
Abstract This research aims to determine the self-confidence of lower service in volleyball learning in students at SMPN 2 Jayakerta, Karawang Regency. This research is a descriptive research, the method used in this research is a survey method and data collection techniques using a questionnaire (questionnaire). The population in this study were all students of class VIII at SMPN 2 Jayakerta, Karawang Regency. This study uses a population sampling technique. Samples of this study were all students of class VIII at SMPN 2 Jayakerta, Karawang Regency, as many as 69 students consisting of 41 male students and 28 female students. Data analysis used descriptive method with percentage calculation. Based on the results of this study, it shows that the low service confidence in volleyball learning for all VIII class at SMPN 2 Jayakerta, Karawang Regency for male students is the greatest in the